Effectiveness of problem gambling interventions in a service setting: a protocol for a pragmatic randomised controlled clinical trial - Abbott, M (BMJ Open, 2017)
INTRODUCTION: The primary purpose of this study is to evaluate the relative effectiveness of 2 of the best developed and most promising forms of therapy for problem gambling, namely face-to-face motivational interviewing (MI) combined with a self-instruction booklet (W) and follow-up telephone booster sessions (B; MI+W+B) and face-to-face cognitive–behavioural therapy (CBT). METHODS AND ANALYSIS: This project is a single-blind pragmatic randomised clinical trial of 2 interventions, with and without the addition of relapse-prevention text messages. Trial assessments take place pretreatment, at 3 and 12 months. A total of 300 participants will be recruited through a community treatment agency that provides services across New Zealand and randomised to up to 10 face-to-face sessions of CBT or 1 face-to-face session of MI+W+up to 5 B. Participants will also be randomised to 9 months of postcare text messaging. Eligibility criteria include a self-perception of having a current gambling problem and a willingness to participate in all components of the study (eg, read workbook). The statistical analysis will use an intent-to-treat approach. Primary outcome measures are days spent gambling and amount of money spent per day gambling in the prior month. Secondary outcome measures include problem gambling severity, gambling urges, gambling cognitions, mood, alcohol, drug use, tobacco, psychological distress, quality of life, health status and direct and indirect costs associated with treatment. ETHICS AND DISSEMINATION: The research methods to be used in this study have been approved by the Ministry of Health, Health and Disability Ethics Committees (HDEC) 15/CEN/99. The investigators will provide annual reports to the HDEC and report any adverse events to this committee. Amendments will also be submitted to this committee. The results of this trial will be submitted for publication in peer-reviewed journals and as a report to the funding body. Additionally, the results will be presented at national and international conferences. TRIAL REGISTRATION NUMBER: ACTRN12615000637549.